Impact of shuai jiao wrestling training on temperament and volitional self-regulation of university students - Pastukhov, I.S.; Timofeeva, O.V.; Lubyshev, E.A.; Kim, L.G. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to conduct a comparative assessment of the impact of Chinese Shuai Jiao wrestling training on the temperament and volitional self-regulation of first-year university students. Methods and structure of the study. Chinese Shuai Jiao wrestling was introduced and tested within the physical education curriculum to experimentally examine its effect on temperament traits and volitional self-regulation. The study involved 120 male first-year students from Patrice Lumumba Peoples’ Friendship University of Russia. The experiment was conducted over one academic year, with sessions held twice a week for two academic hours each. Results and conclusions. No statistically significant differences were found between the groups at the start of the experiment. At its conclusion, it was established that the use of Chinese Shuai Jiao wrestling in the physical education of university students effectively and positively influences the development of temperament traits. Similar results were obtained when examining the levels of volitional self-regulation, as confirmed by statistically significant indicators across all measured parameters.